Análise discursiva da propaganda da absolut vodka - álvares, Thelma Lucia Guerra (2016)
The present study aims to analyze Absolut Vodka s discourse through Absolut Berlin advertisements as well as Absolut Color, Absolut No Label and Absolute Unique s special edition bottles. The adopted theory is French Discourse Analysis and analysis will bethe theoretical framework, since it adopts a dialectical relationship between language and discourse, and presents construction of meanings, highlighting both product and process. The following analysis categories will be addressed to highlight the different discourse effects and representations of the collective imagination, which can be understood by discursive materiality: production conditions, interdiscourse, discursive formation, ideological formation, paraphrase and polysemy. Thus, the objective is to identify the discursive marks in Absolut Vodka s communication, analyze advertising interdiscourse of the brand and evaluate the imaginary and ideological formations. For this study, we relied on the theorists Pêcheux and Orlandi. The corpus consists of an Absolut Berlin advertisement, which refers to the political-ideological question of the fall of the Berlin Wall, Absolut Color and No Label bottles, both of which honors homosexual audiences, and Unique bottle, which relates to identity and individuality. They rely on construction of meanings when employing images for the understanding of messages.